Water Chemistry During Baseflow Helps Inform Watershed Management: A Case Study of the Lake Wister Watershed, Oklahoma. (4th January 2019) - Austin, Bradley J.; Patterson, Steve; Haggard, Brian E.
Abstract: Nonpoint source (NPS) pollution from agricultural and urban development is a primary source of nutrients and decreased water quality in aquatic systems. Installation of best management practices (BMPs) within critical source areas of the watershed can be helpful at reducing the transport of nutrients to waterbodies; however, prioritizing these areas may be difficult. The objective of this study was to develop several potential frameworks for prioritizing subwatersheds using baseflow water chemistry data in relation to a simple human development index (HDI; total percent agriculture and urban development). At a monthly interval, samples were collected at 26 sites throughout the Oklahoma portion of the Lake Wister Watershed (LWW) and analyzed for total nitrogen, total phosphorus, total suspended solids, and chlorophyll a . Changepoint analysis for each parameter found significant thresholds for each of the parameters ranging from 20 to 30% HDI. Changepoint analysis summary statistics were used to develop prioritization frameworks for the LWW that could be used to target subwatersheds where BMP installation would have the greatest effect at improving water quality. Additionally, regression models developed from the relationships between water quality parameters and HDI values serve as realistic targets for improving water quality, with the modeled line representing the target concentration for a given HDI value. After BMPs have been implemented, baseflow monitoring should continue at the subwatershed scale to track changes in water quality. Focusing monitoring efforts at the subwatershed scale will provide an earlier indication of the effectiveness of BMPs, as it may take several decades to detect improvements in water quality at the larger watershed scale.